2007
DOI: 10.2460/ajvr.68.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical evaluation of substance P and calcitonin gene-related peptide in skin and periosteum after extracorporeal shock wave therapy and radial pressure wave therapy in sheep

Abstract: Substance P- and CGRP-containing nerve fibers are not disrupted by EWST or RPWT. Further studies are needed to identify the mechanism of analgesia observed in association with these treatment modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…This suggests that ESWT may suppress inflammation by reducing CGRP and SP. However, contrary to other studies, the results reported by Abed et al found no histological changes in SP- and CGRP-containing nerve fibers in sheep that received ESWT ( 103 ). It suggests that we still need a large accumulation of evidence to prove whether ESWT can really suppress inflammation by affecting CGRP and SP-positive nerve fibers.…”
Section: Biological Responses Caused By Eswt In the Three Phases Of T...contrasting
confidence: 78%
“…This suggests that ESWT may suppress inflammation by reducing CGRP and SP. However, contrary to other studies, the results reported by Abed et al found no histological changes in SP- and CGRP-containing nerve fibers in sheep that received ESWT ( 103 ). It suggests that we still need a large accumulation of evidence to prove whether ESWT can really suppress inflammation by affecting CGRP and SP-positive nerve fibers.…”
Section: Biological Responses Caused By Eswt In the Three Phases Of T...contrasting
confidence: 78%
“…Substance P and CGRP are neuropeptides that are present in small-diameter afferent fibers. They are known to be involved in nociception in both the peripheral and central nervous systems ( 151 ). They can be released from nerve endings and play a pro-inflammatory role in the nerve tissues ( 152 , 153 ).…”
Section: Cellular and Molecular Mechanismmentioning
confidence: 99%
“…The origin of the apparent clinical effect could not be definitively determined. 11 Release of substance P, an endogenous analgesic, may be induced via ESWT, 12 but that hypothesis was not investigated in the present study. Results of our study did not provide any direct explanation for the improvement in lameness score after ESWT, although improvement in the response to carpal flexion provided additional confirmation of the effect of ESWT on reducing clinical signs of OA.…”
Section: Discussionmentioning
confidence: 77%